BIOETHICAL ASPECTS IN THE APPROACH OF THE MINOR PATIENT - GENERAL REVIEW - Andreea Sălcudean; Monica Kiss; Cristina Raluca Bodo; Maria Melania Lica; Elena Gabriela Strete (Amaltea Medical Publishing House, 2021)
The objective of this review was to present the main ethical issues in minor patient healthcare activity including: minor patient consent, parental consent, confidentiality and medical examination. The particular ethical issues that arise in the medical care of children and adolescents overlap with those of other patients, who lack decision-making capacity or have diminished decision-making capacity. Children should always be respected as persons. A consent from the child and parental permission be sought whenever possible, by using appropriate tools. Even minor patient demonstrated the ability to understand essential elements of healthcare activity and the details of the medical examination, there is variability in children's level of understanding, mainly due to their age and maturity. The legal framework in every country represents a guide for the medical doctors and a reference for their patients.